2013
DOI: 10.1523/jneurosci.5889-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Regulation of the K/Cl Transporter KCC2 Membrane Diffusion, Clustering, and Function in Hippocampal Neurons

Abstract: The neuronal K/Cl transporter KCC2 exports chloride ions and thereby influences the efficacy and polarity of GABA signaling in the brain. KCC2 is also critical for dendritic spine morphogenesis and the maintenance of glutamatergic transmission in cortical neurons. Because KCC2 plays a pivotal role in the function of central synapses, it is of particular importance to understand the cellular and molecular mechanisms underlying its regulation. Here, we studied the impact of membrane diffusion and clustering on K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
202
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(216 citation statements)
references
References 78 publications
13
202
1
Order By: Relevance
“…inhibitory synapses, suggestive of stronger confinement of KCC2 to excitatory synapses (Chamma et al . 2013). The stronger confinement may result from interactions between KCC2 and proteins at excitatory synapses.…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 99%
“…inhibitory synapses, suggestive of stronger confinement of KCC2 to excitatory synapses (Chamma et al . 2013). The stronger confinement may result from interactions between KCC2 and proteins at excitatory synapses.…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 99%
“…Phosphorylation of human threonines Thr 906 and Thr 1007 reduced the intrinsic transport activity of KCC2 (37,38). In contrast, phosphorylated Ser 940 increased surface expression and KCC2 transport function (39) as well as membrane clustering (40). Finally, the phosphorylation status of Tyr 903 and Tyr 1087 also regulates KCC2 activity, although the functional consequences of phosphorylation appear to be context-dependent and require further investigation (5,23,36,41,42).…”
mentioning
confidence: 99%
“…4D; p ϭ 0.02). To confirm that GluK2 increases KCC2 expression in the membrane, we performed total internal reflection microscopy (TIRF) 5 in COS-7 cells overexpressing KCC2-HA, which allows the imaging of proteins exclusive to the surface membrane. We observed a signif- Ϫ/Ϫ hippocampal neurons overexpressing KCC2-FLAG.…”
Section: Gluk2 Promotes Kcc2 Recycling To the Neuronal Membranementioning
confidence: 99%
“…In addition to the critical role KCC2 plays in synaptic inhibition, KCC2 is highly localized to excitatory synapses (4,5), where it plays important roles in the development (6) and the function of glutamatergic synapses (7,8). In fact, single-particle tracking revealed that KCC2 is tightly confined to excitatory synapses (5), which may result from local protein interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation